Rationally designed Campylobacter jejuni Cas9 enables efficient gene activation and base editing - Yuxi Chen; Rui Kang; Yuanling Jiang; Qi Zheng; Yue Yang; Jiaqi Liu; Guanglan Wu; Weijun Zhao; Zhan Li; Chengxiang Peng; Pengfei Zhang; Fei Peng; et al. (Elsevier, 2024)
Compact and adaptable CRISPR-Cas systems enable genome engineering applications in various contexts via high-efficiency delivery. The adeno-associated virus (AAV) is a widely used delivery system. One of the most compact type II-C Cas9 orthologs-CjCas9, derived from Campylobacter jejuni, is particularly appealing for AAV delivery. However, the editing efficiency of CjCas9 limits its applications. In this study, we used structure-guided protein engineering to improve the editing efficiency of CjCas9. Subsequently, we developed a miniature transcriptional activator (LDE-CjCas9-VPR) and base editors engineered from CjCas9 (LDE-CjABE and LDE-CjCBE). LDE-CjABE effectively induced genome editing in human and mouse cells. Through AAV delivery, LDE-CjABE enhanced the on-target editing efficiency, and off-target editing was not detected in the mouse retina. Therefore, the compact size and high editing efficiency of LDE-CjCas9 broadens the target scope of transcription activation and base editing toolsets for therapeutic applications.